The contribution of absorption of integral nanocrystals to enhancement of oral bioavailability of quercetin - Baode Shen; Chengying Shen; Weifeng Zhu; Hailong Yuan (Elsevier, 2021)
In this study, self-discriminating hybrid nanocrystals was utilized to explore the biological fate of quercetin hybrid nanocrystals (QT-HNCs) with diameter around 280 nm (QT-HNCs-280) and 550 nm (QT-HNCs-550) following oral and intravenous administration and the contribution of integral nanocrystals to oral bioavailability enhancement of QT was estimated by comparing the absolute exposure of integral QT-HNCs and total QT in the liver. Results showed that QT-HNCs could reside in vivo as intact nanocrystals for as long as 48 h following oral and intravenous administration. A higher accumulation of integral QT-HNCs in liver and lung was observed for both oral and intravenous administration of QT-HNCs. The particle size affects the absorption and biodistribution of integral QT-HNCs and total QT. As compared to QT-HNCs-550, QT-HNCs-280 with smaller particle size is more easily absorbed, but dissolves faster in vivo, leading to higher distribution of QT (146.90 vs. 117.91 h·μg/mL) but lower accumulation of integral nanocrystals (6.8 2e10 vs. 15.27e10 h·[p/s]/[µW/cm²]) in liver following oral administration. Due to its slower dissolution and enhanced recognition by RES, QT-HNCs-550 with larger diameter shows higher liver distribution for both of QT (1015.80 h·μg/mL) and integral nanocrystals (259.63e10 h·[p/s]/[µW/cm²]) than those of QT-HNCs-280 (673.82 & 77.66e10 h·[p/s]/[µW/cm²]) following intravenous administration. The absolute exposure of integral QT-HNCs in liver following oral administration of QT-HNCs are 8.78% for QT-HNCs-280 and 5.88% for QT-HNCs-550, while the absolute exposure of total QT for QT-HNCs-280 and QT-HNCs-550 are 21.80% and 11.61%, respectively. Owing to imprecise quantification method, a surprisingly high contribution of integral QT-HNCs to oral bioavailability enhancement of QT (40.27% for QT-HNCs-280 and 50.65% for QT-HNCs-550) was obtained. These results revealed significant difference in absorption and biodistrbution between integral nanocrystals and overall drugs following oral and intravenous administration of QT-HNCs, and provided a meaningful reference for the contribution of integral nanocrystals to overall bioavailability enhancement.